SISTEM PENGELOLAAN LIMBAH PLASTIK DI INDONESIA - Firman Laili Sahwan (Jurnal Teknologi Lingkungan, 2005)
Plastic recycling activities has been done by nonformal institutions since along time ago especilaly in some big cities in Indonesia. The amount of plastic waste is about 10% to 15% of municipal soild waste. Plastic recycling activities has twoadvantages: (1) reducing the potential damage of environment caused by pollution, and (2) creating the job opportunity for people.